OUTCOME BASED LEARNING: A PANACEA FOR QUALITY EDUCATION - Thote, Prashant; S, Gowri (International Journal of Research -GRANTHAALAYAH, 2021)
The curriculum framework asserts learner to debate, dissent form individual opinion on ideas, systems, practices by nurturing skills to think and reason independently. Participatory learning activity is envisioned as a process whereby learners construct concept through assimilation, absorption, interaction and reflection. In the present paper experiential learning activity are designed to ensure that the students are encouraged to seek out knowledge from their hands-on activity than the text book in their own experiences. In the present paper attempt is made to investigate the impact of conventional method of teaching and experiential learning activities on attainment of knowledge and retention of knowledge in learning redox reaction. Data is collected by using pre-test, post-test and retention test. Instrument is validated by experts. Stratified random method is applied to draw the sample. Totally 50 students participate in the study. Sample is separated into two: control and the study group. Control group is exposed to the conventional chalk and talk method while the students from the study group are exposed to Experiential Learning Activities. The result of the study reveals that there is noteworthy difference in the mean score in learning redox reaction in the scores of pre-test, post-test and retention test between the study group and the control group.